Escherichia coli Biofilm Characteristics on Polymeric Heat Exchanger Surfaces. Issue 6 (27th April 2017) - Pohl, Sebastian; Madzgalla, Marco; Manz, Werner; Bart, Hans-Jörg
Abstract: Time‐dependent effects on the apparent roughness and surface free energy of different polymeric surfaces and stainless steel were studied during the biofouling process for Escherichia coli K12. The surface roughness increases during primary adhesion of E. coli on the surfaces and is later reduced as the surface between scattered bacteria is completely covered, forming a uniform biofilm. During the fouling process, the polar fraction of the surface free energy significantly increased, whereas the dispersive fraction decreased for all substrates. The attachment of E. coli and subsequent bacterial production of extracellular polymeric substances increased the polarity of the initially nonpolar polymeric surfaces to increase wettability. Abstract : Surfaces of polymeric heat exchangers show beneficial biofouling tendencies, compared with those of stainless steel, in applications utilizing river water as a coolant. The measurable surface characteristics of the biofilm change drastically over time and have to be considered in fluid simulations. Correlations between initial roughness and wettability are given with respect to biofilm formation.